Clinical utility of SARS-CoV-2 whole genome sequencing in deciphering source of infection. (January 2021) - Takenouchi, T.; Iwasaki, Y.W.; Harada, S.; Ishizu, H.; Uwamino, Y.; Uno, S.; Osada, A.; Abe, K.; Hasegawa, N.; Murata, M.; Takebayashi, T.; Fukunaga, K.; et al.
Summary: Coronavirus disease 2019 (COVID-19) caused by human severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide problem. From the standpoint of hospital infection control, determining the source of infection is critical. We conducted the present study to evaluate the efficacy of using whole genome sequencing to determine the source of infection in hospitalized patients who do not have a clear infectious contact history. Recently, we encountered two seemingly separate COVID-19 clusters in a tertiary hospital. Whole viral genome sequencing distinguished the two clusters according to the viral haplotype. However, the source of infection was unclear in 14 patients with COVID-19 who were clinically unlinked to clusters 1 or 2. These patients, who had no clear history of infectious contact within the hospital ('undetermined source of infection'), had haplotypes similar to those in cluster 2 but did not have two of the mutations used to characterize cluster 2, suggesting that these 14 cases of 'undetermined source of infection' were not derived from cluster 2. Whole viral genome sequencing can be useful for confirming that sporadic COVID-19 cases with an undetermined source of infection are indeed not part of clusters at the institutional level.